Solar energy technology: Knowledge, awareness, and acceptance of solar energy in Ngada, East Nusa Tenggara, Indonesia - Loy, Nikolaus; Rachmawati, Iva; Karolus, Meike Lusye (International Journal of Sustainable Development & World Policy, 2023)
One of the Indonesian Government’s efforts to meet the target of 23% fulfillment of new and renewable energy by 2030 is to provide solar electricity through government assistance. The priority of solar energy projects by the government, one of which is East Nusa Tenggara. The area is area that has a pretty good potential for solar energy. In addition, the site has a low level of access to electricity in Indonesia. In 2007, solar energy projects through a microgrid system were started and continued with a home system. However, the receiving group is a group that lacks knowledge of new renewable energy and is also economically vulnerable. This research was conducted to identify the level of understanding, awareness, and acceptance of solar energy users, which generally demands good knowledge and economic strength. Questionnaires containing demographic, attention, and approval information to utilize solar PV technology were distributed to 20 selected respondents from Maghilewa, Jere, Watu, and Belaraghi in Ngada, East Nusa Tenggara. The study revealed that although 90% of respondents had no basic knowledge of science, their level of awareness of solar energy technology and its use was at an average score. However, respondents showed a high level of technology acceptance because of the hope for social and economic improvement. In addition, the study also found that respondents in 4 kampongs were deeply involved in the changes that new technology products brought to society. The respondent gives total commitment to using and maintaining solar power.